Pendampingan pembuatan pondasi telapak kantor RW 021 Baktijaya Sukmajaya Depok - Lilis Tiyani; Amalia; Anis Rosyidah; Denny Yatmadi (IKIP SILIWANGI, 2025)
RW 021 is in the Baktijaya sub-district area, Sukmajaya, Depok. This RW area is located approximately 5 km from the Jakarta State Polytechnic campus. This area consists of 10 RTs, with an average number of 120 families per RT. The problem faced by RT 021 residents is that they do not have a building or meeting room for community activities. Until now, RW 021's activities have been taking place in residents' homes. These activities include posyandu, PKK activities, counseling and other activities. Due to the absence of these facilities, residents' activities are hampered. The location for the RW 021 Building is already in the RT 06 area. However, until now there has been no funding to start building the building. To help the residents of RW 021 build the building, assistance was provided to the residents as well as applying the results of research on SCC concrete with blended cement to create the footing foundation for the office building. The aim of this activity is to provide assistance and apply the results of research on SCC concrete with blended cement to make the f footing foundation for the building that meets RW 021, Baktijaya, Sukmajaya, Depok. The method used to achieve the above goal is to provide assistance to residents in making footing foundations using SCC blended cement concrete mixture. The result of this activity was the construction of the entire footing foundation for the RW 021 office, in accordance with the plan drawings